1961
DOI: 10.1104/pp.36.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Changing respiratory pathways in potato tuber slices

Abstract: The test solutions wvere of two formulations, for controls (C), and for malonate treatments (M).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
34
0
2

Year Published

1962
1962
1978
1978

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 26 publications
2
34
0
2
Order By: Relevance
“…By contrast, malonate-resistant fresh potato disks normally become increasingly malonate-sensitive with time (10,19). However, when storage organ slices are aged in bicarbonate under 5 to 10 % CO2 in air, the respiration rises as normally but remains malonate-resistant (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, malonate-resistant fresh potato disks normally become increasingly malonate-sensitive with time (10,19). However, when storage organ slices are aged in bicarbonate under 5 to 10 % CO2 in air, the respiration rises as normally but remains malonate-resistant (11).…”
mentioning
confidence: 99%
“…One way to estimate and characterize respiratory activity is to observe the utilization and disposition of radioactive substrate provided exogenously at levels sufficiently low so that hopefully the metabolite provided serves to label the endogenous metabolic pool without significantly altering the latter. It was early noted that when fresh and aged potato slices were compared with respect to the utilization of C14-labeled glucose, the evolution of C1402 differed very much more markedly than did gross glucose absorption (10,19). Since a pronounced enhancement of salt absorbing capacity is known to accompany the respiratory rise which attends aging (12,13), the question arose as to whether apparent differences in glucose utilization reflected distinctions related to glucose absorption.…”
mentioning
confidence: 99%
“…Ap Rees and Beevers (1), who suggested that pentose phosphate metabolism is largely responsible for the respiratory increase, allowed light from normal laboratory conditions to strike the aging slices. Romberger and Norton (12), on the other hand, indicated that culturing (aging) was carried out in the dark and have interpreted their results to indicate that the tricarboxylic acid cycle becomes enhanced with aging. The latter conclusions were also reached by Laties (8), although light conditions were not reported.…”
mentioning
confidence: 99%
“…\Vhen inhibitioni of C-6 release by-malonate is first manifest, the evolution of C"4O. fromii C-1 labelecl glucose becomes malonate-sensitive for the first time (22). C) Agedl slices presente(l xvith uniformly labeledI glucose-Cl accumlulate labeled succinate in the presence of malonate.…”
mentioning
confidence: 99%
“…A) While a variable modlicum of fresh slice respiration nlay prove malonate-sensitive, fresh tissue respiration is predominantly malonate-resistant. By contrast, the respiratory increment which arises Nvith aging is alimlost 1 Received Oct. 16, 1963. totally malonate sensitive (22). B) Fresh slices release C-1 of 1-C14 labeledl glucose as CO., but fail to release radioactive CO., fronm 6-Cl4 labeled glucose.…”
mentioning
confidence: 99%